Urban mobility as a product of an evolutionary system (2011)
Urban mobility has become a principal concern for most cities around the world. Several policies have been implemented by planners hoping to mitigate the immobility problem. However, many of these policies have not produced the desired effect in cities' mobility conditions. Furthermore, urban populations will continue to grow, more people will need to move around a city and space for mobility will continue to be a scarce resource; hence, tackling the urban mobility problem successfully requires effective policies that mitigate the immobility problem. This project focuses on understanding urban mobility as a product of an evolutionary system. The aim is to offer an alternative way of approaching the situation such that it that permits the formulation of policies that generate a positive impact on the urban immobility problem. The advantages and implications of understanding the situation from this perspective are also evaluated.